Evaluation of the effects of sildenafil citrate (viagra) on canine renal artery, carotid and aortic blood flow with the aid of color Doppler sonography - Serhatlioglu, S; Kiris, A; Kocakoc, E; Canpolat, I; Bozgeyik, Z; Han, MC (Karger, 2003)
Introduction: Erectile dysfunction is the inability to achieve or maintain an erection sufficient for satisfactory sexual performance. Oral use of sildenafil citrate has been proved to be effective in the treatment of erectile dysfunction. Although the effects of sildenafil citrate have been investigated in several studies, its effect on aortic, carotid and renal artery blood flow is unknown. The aim of this study was to investigate the early and late phase effects of sildenafil citrate on canine aortic, carotid and renal artery blood flow using color Doppler sonography (CDS). Materials and Methods: A total of 6 healthy adult dogs was used in this study. With the aid of CDS peak systolic flow rate, end diastolic flow rate, resistivity index (RI) and pulsatility index in aortic, renal and carotid artery were determined before the administration of sildenafil citrate, 45-75 min after drug administration and after 15 days of drug administration. Data were statistically analyzed using Friedman and Wilcoxon rank tests. p < 0.05 was considered to be statistically significant. Results and Conclusions: Significant changes were determined in only 4 out of 28 parameters studied. The significantly changed parameters were as follows: a significant increase in the early and late phase of the postdrug peak of systolic aortic blood flow compared to values before drug administration, an increase in pre- and postdrug RI values of the aorta, a significant decrease in maximum velocity of the right carotid artery, and peak systolic maximum velocity of the left renal segmental artery after drug administration compared to their respective predrug basal values. The results from this study indicate that sildenafil citrate has no significant effects on aortic, renal and carotid artery blood flow rate either in the early or in the late phase. Since this study involved only 6 dogs there is a need for further clinical studies involving larger groups of subjects to conclude that this drug is safe with respect to the hemodynamic parameters evaluated in this study. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: sildenafil sitrate; Doppler sonography; carotid artery; aorta